THE INFLUENCE OF COUNTRY-OF-ORIGIN IMAGE, BRAND IMAGE, AND BRAND EVALUATION ON PURCHASE INTENTION TOWARDS NIKE BRAND IN JABODETABEK - Mujahidah, As Syifa; Tan, Pauline Henriette Pattyranie (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2021)
Abstract: The athletic footwear industry is growing rapidly in both global and domestic markets, and one of the major global brand players is Nike, which holds the largest market share in the world, followed by Adidas. However, this did not happen in the Indonesian market where Nike was beaten by Adidas to take second place. The difference in this condition is interesting to investigate further about the factors that can influence the buying interest of Indonesian consumers towards the Nike brand, especially in the Greater Jakarta area. Therefore, further research was conducted to determine whether the image of the country of origin, brand image, and brand evaluation could influence purchase interest, through data from 220 respondents who live in Jabodetabek. The hypothesis tested using PLS-SEM shows that all variables have a positive correlation in influencing consumer purchase intentions of the Nike brand, except for the country of origin. The findings in this study will be of great benefit to consumers, marketers and researchers in the future, especially those involved directly and indirectly with the United States and the Nike brand.Â Abstrak: Industri alas kaki atletik berkembang pesat baik di pasar global maupun pasar domestik, dan salah satu pemain merek global utama adalah Nike, yang memegang pangsa pasar terbesar di dunia, diikuti oleh Adidas. Namun hal tersebut tidak terjadi di pasar Indonesia dimana Nike dikalahkan oleh Adidas untuk menempati posisi kedua. Perbedaan kondisi ini menarik untuk diteliti lebih jauh mengenai faktor-faktor yang dapat mempengaruhi minat beli konsumen Indonesia terhadap merek Nike, khususnya di wilayah Jabodetabek. Oleh karena itu, penelitian lebih lanjut dilakukan untuk mengetahui apakah citra negara asal, citra merek, dan evaluasi merek dapat mempengaruhi minat beli, melalui data dari 220 responden yang berdomisili di Jabodetabek. Hipotesis yang diuji menggunakan PLS-SEM menunjukkan bahwa semua variabel memiliki korelasi positif dalam mempengaruhi niat beli konsumen atas merek Nike, kecuali negara asal. Temuan dalam studi ini akan sangat bermanfaat bagi konsumen, pemasar, dan peneliti di masa mendatang, terutama yang terlibat langsung dan tidak langsung dengan Amerika Serikat dan merek Nike.